Seroprevalence of anti-SARS-CoV-2 IgG antibodies in HIV-positive and HIV-negative patients in clinical settings in Douala, Cameroon - Kwedi Nolna, Sylvie; Niba, Miriam; Djadda, Cedric; Masumbe Netongo, Palmer (Frontiers in Epidemiology, 2023)
The asymptomatic nature of COVID-19 coupled with differential testing are confounders in the assessment of SARS-CoV-2 incidence among PLWH. As various comorbidities increase the risk of SARS-CoV-2 infection, it is crucial to assess the potential contribution of HIV to the risk of acquiring COVID-19. Our study aimed to compare the Anti-SARS-CoV-2 IgG seroprevalence among people living with and without HIV. Methods: PLWH were enrolled in HIV units of two health facilities in Douala. Participants were consecutively enrolled among whom 47 were people living with HIV and 31 HIV negative patients. SARS-CoV-2 antibody tests were performed on all participants. Overall, medical consultation was conducted. For HIV-Positiveparticipants only, viral load, antiretroviral regimen, duration of HIV infection, and duration of antiretroviral treatment were retrieved from medical records.We found an overall SARS-CoV-2 IgG seroprevalence of 42.31% compared to 44.6% for PLWH and 38.7% among those without HIV infection with no statistically significant difference. Adjusting for sex, HIV status, and BCG vaccination, the odds of previous SARS-CoV-2 infection were higher among married persons in the study population. Gender, BCG vaccination, and HIV status were not found to be associated with SARS-CoV-2 IgG seropositivity.Our findings support the lack of association between HIV status and susceptibility to SARS-CoV-2 infection. The ARV regimen, suppressed viral load, and Tenofovir boasted ARV regimen might not affect the body's immune response after exposure to SARS-CoV-2 among PLWH. Thus, if HIV is well treated, the susceptibility to COVID-19 in PLWH would be like that of the general population.